Hubungan Sumber Informasi Dan Sikap Ibu Terhadap Kelengkapan Imunisasi Dasar Pada Balita Di Wilayah Kerja Puskesmas Pulau Kupang Kuala Kapuas: Relationship Between Sources of Information and Mother's Attitude Towards The Completeness of Basic Immunization for Toddlers in The Working Area of The Pulau Kupang Kuala Kapuas Health Center - Hidayah, Nurul; Desilestia Dwi Salmarini; Sarkiah; Nita Hestiyana (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2024)
Immunization is an effort to actively reduce the number of morbidity, mortality and disability due to Immunization Preventable Diseases (PD3I). The role of parents, especially a mother in the immunization program is very important. Therefore, sources of information and attitudes influence the awareness of mothers to bring their toddlers for immunization. To find out the relationship between information sources and mothers' attitudes towards the completeness of basic immunization for toddlers in the working area of the Pulau Kupang health center. Quantitative research using a cross sectional approach. The research population was toddlers aged 12-24 months using purposive sampling technique. The measuring tool used is a questionnaire whose results are analyzed using the fisher exact test. Respondents with sufficient sources of information and complete immunization were 16 under five, the results of the fisher exact test showed a p value of 0.019. Meanwhile, respondents with a positive attitude who carried out complete immunization were 24 toddlers and 2 toddlers incomplete. fisher exact test results show a p value of 0.010. Sources of information and mother's attitude have an influence on the completeness of basic immunization for toddlers in the work area of Pulau Kupang Kuala Kapuas Public Health Center ABSTRAK Imunisasi adalah upaya untuk menekan jumlah kesakitan, kematian dan kecacatan secara aktif akibat Penyakit yang Dapat Dicegah Dengan Imunisasi (PD3I). Peran orangtua terutama seorang ibu pada program imunisasi sangatlah penting. Oleh karena itu, sumber informasi dan sikap berpengaruh terhadap kesadaran ibu untuk membawa balitanya melakukan imunisasi. Mengetahui hubungan sumber informasi dan sikap ibu terhadap kelengkapan imunisasi dasar pada balita di wilayah kerja Puskesmas Pulau Kupang. Penelitian kuantitatif menggunakan pendekatan Cross Sectional. Populasi penelitian balita usia 12 - 24 bulan dengan teknik Purposive Sampling. Alat ukur yang digunakan berupa kueisoner yang hasilnya dianalisis menggunakan uji Fisher Exact. Responden dengan sumber informasi cukup dan imunisasi lengkap sebanyak 16 balita. Hasil uji fisher exact menunjukkan nilai p value sebesar 0,019. Sedangkan responden dengan sikap positif yang melakukan imunisasi lengkap ada 24 balita dan tidak lengkap 2 balita. Hasil uji Fisher Exact menunjukkan nilai p value sebesar 0,010. Sumber informasi dan sikap ibu memiliki pengaruh terhadap kelengkapan imunisasi dasar pada balita di wilayah kerja Puskesmas Pulau Kupang Kuala Kapuas.